DAMPAK PERUBAHAN BUDAYA DI DAERAH KABUPATEN BUTON TENGAH TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Haliadi; Naya; Nur Aina; Nur Ismail (CV. Adiba Aisha Amira, 2026)
The purpose of this study is to examine the impact of cultural changes on the educational process in the Dasar school in Kabupaten Buton Tengah. The changes brought about by globalization, technological advancement, and social mobility have an impact on sikap, nilai, and student learning. Three main schools—SD Negeri 1 Mawasangka, SD Negeri 6 Mawasangka, and SD Negeri 17 Mawasangka—were used for the study, which examined the characteristics of schools in semi-perdesaan and pusat pemerintahan. This study used a deskriptif kualitatif approach using observational and wawancara data collection techniques. The study's findings indicate that changes in culture have both positive and negative effects on learning. Positive effects can be shown in students' increased interest in learning new things, communication skills, and using technology in the classroom. Even however, negative effects are caused by a decrease in local customs, a decrease in the use of the daerah language, and a melemah-like approach to learning. The teacher responds to this situation by incorporating local customs and traditions into thematic instruction and character education. The findings of this study indicate that cultural change is a keniscayaan that has to be addressed by contextual learning strategies that balance local and global impacts.